PENYULUHAN KELAINAN DEGENERATIF DI BIDANG ORTHOPEDI MELALUI SENAM OSTEOPOROSIS - Humaryanto, Humaryanto; Justitia, Budi; Mulyadi, Deri; Husnul, Husnul; Nuriyah, Nuriyah (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2024)
ABSTRACTAn important aspect in improving quality of life is bone and joint health, especially as you age. Degenerative disorders in orthopedics such as osteoporosis have become a significant public health problem. Osteoporosis is characterized by a decrease in bone density, increasing the risk of bone fractures and causing various serious complications. For this reason, the service team carried out an activity in the form of counseling and osteoporosis exercises as well as conducting consultations regarding the participants' current disease complaints, especially problems related to osteoporosis in the sub-district services of the city across Jambi. Increase knowledge about degenerative diseases and types of food that are related to the causes of osteoporosis. This begins with osteoporosis exercises and continues with education about degenerative disorders and types of food related to osteoporosis. Participants were given pretest and posttest questions to measure knowledge about degenerative disorders and types of food related to osteoporosis. There was an increase in the number of correct points during the post-test compared to the pretest.Key words: degenerative disorders, osteoporosis, nutrition ABSTRAKAspek penting dalam meningkatkan kualitas hidup adalah Kesehatan tulang dan sendi terutama ditengah pertambahan usia. Kelainan degeneratif di bidang orthopedi seperti osteoporosis telah menjadi masalah Kesehatan masyarakat yang cukup signifikan. Osteoporosis yang ditandai dengan penurunan kepadatan tulang, meningkatkan risiko patah tulang dan menimbulkan berbagai komplikasi serius. Untuk itu tim pengabdian melakukan suatu kegiatan berupa penyuluhan dan senam osteoporosis serta melakukan konsultasi mengenai keluhan penyakit peserta yang saat ini dirasakan terutama masalah yang berkaitan dengan osteoporosis di kecamatan pelayangan kota seberang jambi. Tujuan meningkatkan pengetahuan tentang penyakit degeneratif dan jenis makanan yang berhubungan dengan penyebab terjadinya osteoporosis. Metode kegiatan ini diawali senam osteoporosis dan dilanjutkan penyuluhan kelainan degeneratif dan jenis makanan yang berhubungan dengan osteoporosis. Peserta diberikan soal pretest dan postest untuk mengukur pengetahuan tentang kelainan degenerative dan pola makan yang berhubungan dengan osteoporosis. Hasil terdapat peningkatan jumlah benar saat post-test dibandingkat pretest. Kata kunci: kelainan degenerative, osteoporosis, gizi